2011
DOI: 10.1093/aob/mcr233
|View full text |Cite
|
Sign up to set email alerts
|

Elusive but not hypothetical: axillary meristems in Wollemia nobilis

Abstract: In this Viewpoint, I argue that Tomlinson and Huggett do not refer to previously published information that indicates that axillary meristems are present in Wollemia nobilis branch leaf axils, and that their anatomical methods were probably not optimal for locating and examining these minute structures. Thus, whilst I would agree that the axillary meristems in branch leaf axils of Wollemia nobilis are elusive, I contend that they are not hypothetical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We appreciate the opportunity, provided by the Chief Editor, to respond hermeneutically to the critique by Burrows (2012) of our paper on branch regeneration in plagiotropic axes of Wollemia nobilis, where we claim that reiterated axes do not necessarily arise from axillary growth centres referred to as 'axillary meristems' (Tomlinson and Huggett, 2011). Our observations did not indicate that these existed in our material prior to manipulative techniques that generated new shoots behind decapitated axes.…”
mentioning
confidence: 85%
“…We appreciate the opportunity, provided by the Chief Editor, to respond hermeneutically to the critique by Burrows (2012) of our paper on branch regeneration in plagiotropic axes of Wollemia nobilis, where we claim that reiterated axes do not necessarily arise from axillary growth centres referred to as 'axillary meristems' (Tomlinson and Huggett, 2011). Our observations did not indicate that these existed in our material prior to manipulative techniques that generated new shoots behind decapitated axes.…”
mentioning
confidence: 85%
“…They suggested that persistent meristems in these axils were hypothetical. They used 60-90 µm thick sections, which was not ideal when searching for structures only 45-75 µm in diameter [65]. In addition, they overlooked information that indicated persistent axillary meristems had already been described and illustrated in leaf axils of first order branches of wollemi pine [61,65].…”
Section: Araucariaceaementioning
confidence: 99%